A Study on Development of a New Concept Cargo River Ship with Reduced Resistance Acting on Hull in Calm Water - Ngo, Van He (Old Journal, 2017)
In this paper, a new hull form is developed for the cargo river ship with a drastically reduced viscous resistance by using Air Circular Tank (ACT) and small air resistance hull form by using CFD (Computation Fluid Dynamic). At first, viscous resistance acting on the new hull is calculated and compared with those of the experimental results to validate the CFD results. Then, ACT is attached on the ship, resistance acting on the new hull is computed by the CFD. Simulated results as pressures distribution around hull, viscous resistance acting on the hull with and without ACT are compared at others. Secondly, air resistance is computed by the CFD. From results of pressure, velocity distribution around hull and air resistance, a new hull shape is developed. The CFD results as pressure distribution and resistances are useful to understand what happened at the ACT. And so on, the problems as the interaction effects between accommodation and hull, effects of hull shape on resistances are found in this paper.